Impact evaluation design for the CHED K-to-12 transition program - Michael R. Cabalfin; Ruzzel Brian C. Mallari; Aniceto C. Orbeta (Philippine Institute for Development Studies (PIDS), 2019)
The Enhanced Basic Education Act of 2013, among others, added two years in secondary education thereby delaying entry into higher education by two years. This was expected to displace teaching and non-teaching personnel in higher education. To mitigate the impact, the law mandated the Commission on Higher Education (CHED), the Department of Education (DepEd) and the Technical Education and Skills Development Authority (TESDA) to develop and implement adjustment programs. The CHED K to 12 Transition program is one of those programs. This paper describes an impact evaluation design for the CHED K to 12 Transition Program. It focuses on two of the biggest components of the program, namely, (a) the scholarships for graduate studies, and (b) the institutional development and innovation grants. The scholarships for graduate studies aim to enhance the knowledge and skills of higher education institution personnel and improve the quality of teaching in higher education. Given the limited coverage of the program, the selection of participants based on certain criteria summarized into a score that can be ranked and the supposed cut-off score, and the phasing of program implementation, the most appropriate evaluation strategy is regression discontinuity design. The Institutional Development and Innovation Grant, on the other hand, aims to enhance the quality of higher education institutions, among other things, by helping them improve their accreditation level, acquire centers of development and excellence status, autonomous and deregulated status, and in their quest for global competitiveness. Given similar considerations, the proposed evaluation method is also the regression discontinuity design. The paper also describes the next steps in implementing the impact evaluation.
Keywords: 330; Higher Education; K to 12; Scholarships; Institutional Development; Innovation